Management of MEN1 Related Nonfunctioning Pancreatic NETs: A Shifting Paradigm. Issue 6 (June 2018) - Nell, Sjoerd; Verkooijen, Helena M.; Pieterman, Carolina R. C.; de Herder, Wouter W.; Hermus, Ad R.; Dekkers, Olaf M.; van der Horst-Schrivers, Anouk N.; Drent, Madeleine L.; Bisschop, Peter H.; Havekes, Bas; Borel Rinkes, Inne H. M.; Vriens, Menno R.; et al.
Abstract : Objective: To assess if surgery for Multiple Endocrine Neoplasia type 1 (MEN1) related nonfunctioning pancreatic neuroendocrine tumors (NF-pNETs) is effective for improving overall survival and preventing liver metastasis. Background: MEN1 leads to multiple early-onset NF-pNETs. The evidence base for guiding the difficult decision who and when to operate is meager. Methods: MEN1 patients diagnosed with NF-pNETs between 1990 and 2014 were selected from the DutchMEN1 Study Group database, including > 90% of the Dutch MEN1 population. The effect of surgery was estimated using time-dependent Cox analysis with propensity score restriction and adjustment. Results: Of the 152 patients, 53 underwent surgery and 99 were managed by watchful waiting. In the surgery group, tumors were larger and faster-growing, patients were younger, more often male, and were more often treated in centers that operated more frequently. Surgery for NF-pNETs was not associated with a significantly lower risk of liver metastases or death, [adjusted hazard ratio (HR) = 0.73 (0.25–2.11)]. Adjusted HR's after stratification by tumor size were: NF-pNETs <2 cm = 2.04 (0.31–13.59) and NF-pNETs 2–3 cm = 1.38 (0.09–20.31). Five out of the 6 patients with NF-pNETs >3 cm managed by watchful waiting developed liver metastases or died compared with 6 out of the 16 patients who underwent surgery. Conclusions: MEN1 patients with NF-pNETs <2 cm can be managed by watchful waiting, hereby avoiding major surgery without loss of oncological safety. The beneficial effect of a surgery in NF-pNETs 2 to 3 cm requires further research. In patients with NF-pNETs >3 cm, watchful waiting seems not advisable.